Tangible Resources and Effective E-Learning Implementation in Selected Ugandan Public Universities - Mugizi, Wilson (Education Quarterly Reviews, 2023)
This study assessed the influence of tangibles resources on the effective implementation of e-learning during and beyond the COVID-19 pandemic era in public universities in Uganda. The concept of tangible resources was based on Resource Based View Theory. Universities' tangible resources for e-learning were operationalized in terms of ICT teaching facilities, access to ICT facilities, e-library resources, and university ICT implementation policies. Using a cross-sectional survey design, data were collected from a sample of 312 academic staff using a questionnaire survey. Data were analysed using descriptive statistics and structural equation modeling (SEM). The findings revealed that access to ICT facilities and university ICT policy positively and significantly predicted e-learning implementation. However, ICT teaching facilities and libraries e-resources positively but insignificantly predicted e-learning implementation. The conclusions of the study were to the effect that access to ICT facilities and universities' ICT policies are imperative for the implementation of e-learning. Nevertheless, ICT teaching facilities and libraries' e-resources do not necessarily lead to the effective implementation of e-learning. The study recommended that university managers should make effort to ensure that ICT facilities are accessible to lecturers and students, and develop policies guiding the implementation of e-learning. University managers should also make university ICT resources and library e-resources more accessible to lecturers and students.
Keywords: Access; E-Library; Facilities; ICT; Implementation; Policies; RBVT; Resources; Tangibles; Teaching